2013
DOI: 10.1080/10407782.2013.836013
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Forced Convection in a Horizontal Channel with Heated Blocks Due to Oscillation of Incoming Flow

Abstract: Numerical investigation of the hydrodynamic amplification and thermal instabilities by imposing pulsation during forced convection of air cooling of nine identical heated blocks mounted on a horizontal channel is presented. The finite volume method has been used to solve the governing equations. The feature of this work is a narrowband of frequencies, where the enhancement of heat transfer of all electronic components is in the range of 25%-55% compared with steady nonpulsation flow is obtained. Good agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This phenomenon clearly illustrates the existence of the optimum frequency for the maximum heat transfer enhancement. The previous works show that the boundary layer thickness becomes much thinner as Strouhal and Reynolds number are increased [23,27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon clearly illustrates the existence of the optimum frequency for the maximum heat transfer enhancement. The previous works show that the boundary layer thickness becomes much thinner as Strouhal and Reynolds number are increased [23,27].…”
Section: Resultsmentioning
confidence: 99%
“…The governing equations are discretized using the finite volume method while the coupling between velocity and pressure fields is done using the SIMPLER algorithm [27]. The components of velocity ( U and V ) were stored at the staggered locations, and the scalar quantities ( P and θ ) were stored in the centers of these volumes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat transfer problem is important because of its many industrial applications, like cooling of electronic systems, aeronautics and compact heat exchangers [1][2][3][4]. Literature survey shows that most of the existing studies of turbulent flow in horizontal channel with an internal arrangement of rectangular blocks are related to forced or mixed convection phenomenon [5][6][7][8] for the objective of improving the heat transfer rate and the understanding of the fundamental flow interactions mechanisms occurring in various industrial technologies. However, many investigations focused on the modeling and optimization of mounted bars and fins along the channel walls to determine the optimum fin height, aspect ratio and spacing between the blocks to obtain a maximum thermal dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Bouttout and colleagues conducted a numerical study on a horizontal channel mounted with identically heated blocks exposed to forced convection pulsating flow. They concluded that the heat transfer coefficient was enhanced by pulsation of flow.…”
Section: Introductionmentioning
confidence: 99%